Malt1 self‐cleavage is critical for regulatory T cell homeostasis and anti‐tumor immunity in mice. Issue 10 (7th August 2018) - Baens, Mathijs; Stirparo, Rocco; Lampi, Youlia; Verbeke, Delphine; Vandepoel, Roel; Cools, Jan; Marynen, Peter; de Bock, Charles E.; Bornschein, Simon
Abstract: Mucosa‐associated lymphoid tissue 1 (Malt1) regulates immune cell function by mediating the activation of nuclear factor κB (NF‐κB) signaling through both its adaptor and proteolytic function. Malt1 is also a target of its own protease activity and this self‐cleavage further contributes to NF‐κB activity. Until now, the functional distinction between Malt1 self‐cleavage and its general protease function in regulating NF‐κB signaling and immune activation remained unclear. Here we demonstrate, using a new mouse model, the importance of Malt1 self‐cleavage in regulating expression of NF‐κB target genes and subsequent T cell activation. Significantly, we further establish that Treg homeostasis is critically linked to Malt1 function via a Treg intrinsic and extrinsic mechanism. TCR‐mediated Malt1 proteolytic activity and self‐cleavage was found to drive Il2 expression in conventional CD4 + T cells, thereby regulating Il2 availability for Treg homeostasis. Remarkably, the loss of Malt1‐mediated self‐cleavage alone was sufficient to cause a significant Treg deficit resulting in increased anti‐tumor immune reactivity without associated autoimmunity complications. These results establish for the first time that inhibition of MALT1 proteolytic activity could be a viable therapeutic strategy to augment anti‐tumor immunity. Abstract : Genetic ablation of Malt1 self‐cleavage in transgenic mice results in decreased Il2 production and reduced regulatory T cells homeostasis. Significantly, this reduction of regulatory T cell numbers did result in an increased anti‐tumour effect due to increased immune surveillance but retains a level above the threshold that triggers autoimmunity.